Atomic structure of superconductor YBa2Cu3O7-x in field ion microscope; Journal de Physique; Vol. 49-C6 - Mesyats G. A. Gennady Andreyevich; Syutkin N. N.; Ivchenko V. A.; Talantsev E. F. (1988, 1988)
В фонде НТБ ТПУ отсутствует